Variações morfométricas de Ectatomma permagnum Forel, 1908 (Formicidae: Ectatomminae) sob o efeito de fatores ambientais no Cerrado - ANNE GABRIELLE VELICK SANDIM (2022)
The objective of this work is to evaluate the possible morphological changes of different populations of Ectatomma permagnum that occurred in response to environmental changes in urban fragments of Cerrado, evaluating whether i) there is a proportion of the size of the legs in relation to the body according to the size theory -grain, ii) compare morphometric measurements of legs and body to verify if the proportion is influenced by environmental variables responsible for litter formation and heterogeneity, and iii) verify if environmental heterogeneity influences the size of morphological characteristics used for foraging and predation . We used 844 individuals of E. permagnum from four urban fragments with different types of Cerrado vegetation, where 11 morphological measurements of the head, body and legs were measured to describe the morphometry, as well as seven environmental variables of the areas to characterize the environment. For data analysis, i) Weber measurement and total leg measurement were used, comparing the average of the values ​​found, performed t-test and linear regression to confirm the allometry relationship ii) NMDS and MANOVA to differentiate the areas considering the morphometric features. iii) PCA to analyze the contribution of each characteristic to differentiate the fragments and iv) to verify the influence of environmental variables on morphological characteristics, CCA was performed. The total leg length in relation to Weber's length corroborated the grain-size hypothesis. Considering the MANOVA results, there is a significant difference between the fragments when compared with all morphometric variables. In the results of the PCA analysis, the morphological characteristics that most contributed to the distinction between the groups of fragments were the size of the femur and the length of the Weber. The canonical correspondence did not present a significant result between the axes, showing that the heterogeneity of the sampled areas does not influence the sizes of the characteristics measured in the work. Our work also showed that environmental variables do not significantly influence the size of structures, we can assume that other factors can act together with environmental variables on the morphometry of individuals. The low values ​​of standard deviation for the characteristics of the individuals of the Secret show that there is no dispersion of measurements as in other areas, showing a homogeneity in the size of the morphological characters. We conclude that E. permagnum individuals corroborate the grain-size hypothesis, thus confirming a positive allometry for the species. Our morphometric measurements did not show a significant influence of environmental variables, leading us to believe that other internal and external factors may also be important to modify the environment of each fragment, thus selecting the characters of the individuals.